MECHANISM FOR HANDLING CASES OF GENERAL CRIMINAL ACTS OF VIOLENT THEFT BY PROSECUTORS IN BATAM STATE PROSECUTORS - Thiara Dewi Purnama; Rahmi Ayunda (Universitas Internasional Batam, 2022)
The crime of violent theft is the act of a person to injure the victim with the aim that the goods taken remain in the victim's power. Batam State Prosecutor is an agency engaged in law enforcement under the mandate of the